การผ่าตัดเลือดคั่งในสมองและการห้ามเลือดในสมองผ่านกล้อง endoscope โดยใช้นวัตกรรมอุปกรณ์และเทคนิคประยุกต์ ในโรงพยาบาลมหาราชนครราชสีมา - แสงศิริทองไชย เชิดศักดิ์ (Thai Journal of Neurological Surgery, 2025)
Objective: Minimally invasive endoscopic hematoma removal is a new technique, not widely used in the treatment of intracerebral hemorrhage in Thailand. The primary objective of this study is to report case series outcome and applied technique after endoscopic removal of ICH at Maharat Nakorn Rachasima Hospital. The secondary objective is to compare those results with the standard craniotomy technique. Method: We retrospectively reviewed the medical records of patients underwent endoscopic removal of ICH between September 2020 and February 2021 at Maharach Nakorn Rachasima Hospital. The outcome of endoscopic removal of ICH was categorized and analyzed by location, sized of ICH and midline shift measured by brain CT scan. Result: A total of 10 patients (4 men and 6 women) with a mean age of 59 years (range: 28–81 years). Four patients (4/10) had a history of hypertension. As for the location of the hematomas in the 10 ICH cases, there were 7 in the basal ganglia, two in the lobar occipital, and one in the lobar frontal area. The mean preoperative ICH volume was 61 ml. (range: 30–109 ml.), with a mean reduction in ICH volume of 85% (range: 68.6-96.7%). The mean preoperative amounts of midline shift were 0.7 cm (range: 0.0 –1.4 cm.) with a mean reduction in midline shift of 61.4% (range: 40-80%). The mean operation time was 76.6 minutes (range: 45 -120 minutes). The mean length of hospital stay was 22.7 days (range: 6–50 days). Compared with the craniotomy group, the craniotomy group endoscopic group reported a shorter operative time, and lower mortality rates, but longer length of hospital stay. Conclusions: Endoscopic removal of ICH with applied technique appears to be a safe and effective interventional treatment. However, further validation on a larger sample size is required.